RESULTS OF AN ESTIMATION OF EFFICIENCY OF INTERACTION IN PAIRS OF PILOTS WITH USE V. V. GULENKO'S INTERTYPES RELATIONS AND RESULTS OF THE SPECIAL COMPUTER TESTS - A. V. Malishevskiy; P. E. Brovkin (Научный вестник МГТУ ГА)
In this article, we studied results of an estimation of efficiency of interaction in pairs of pilots with use V.V. Gulenko's intertypes relations. It is analysis of results of series of experiments, which have been during 2003–12. In this article, we give the correlations of the received socionic parameters with results of color's sociometry by Etkind A. M., and results of the special computer tests.